Audit committees, non-audit services, and auditor reporting decisions prior to failure. Issue 2 (June 2016) - Wu, Chloe Yu-Hsuan; Hsu, Hwa-Hsien; Haslam, Jim
Abstract: This study investigates the associations between audit committee characteristics and the likelihood of auditors' going-concern decisions among UK failed firms. Specifically, we examine whether the threat posed by auditor-provided non-audit services (NAS) to auditors' reporting decisions is mediated by audit committee characteristics. We find that failed firms with higher proportions of independent non-executive directors (NEDs) and financial experts on the audit committee are more likely to receive auditor going-concern modifications prior to failure, but that there is no significant relationship between NAS fees and the likelihood of receiving a going-concern modification. The evidence further suggests that the association between NAS and auditors' reporting decisions is subject to audit committee characteristics. Where the audit committee is more independent and includes a greater proportion of financial experts, auditors providing the client with NAS are less likely to issue a standard unmodified going-concern report prior to failure. Overall, the findings provide support for corporate governance regulators' concerns about the monitoring benefits of audit committee independence and the presence of financial expertise on the audit committee for auditors' reporting decisions.